COMPARATIVE ANALYSIS OF MARKET OVERREACTION IN INDONESIA AND SINGAPORE STOCK EXCHANGE 2016-2019 - Meiliani, Mutia; Puspita, Dian; Tarigan, Milda Aprilina; Fathoni, Ahmad Fauzan (Program Pascasarjana, Universitas Riau, 2021)
This study aims to determine whether there is a market overreaction phenomenon in the Indonesia Stock Exchange which is classified as an emerging market and the Singapore Stock Exchange which is classified as a developed market. This research was conducted in a weekly period during 2016-2019. This study uses sample included in the LQ-45 index for the Indonesia Stock Exchange and the top 30 market cap for the Singapore Stock Exchange. This research found that there was a market overreaction in the Indonesia Stock Exchange, especially the loser portofolio which experienced the strongest reversal. Meanwhile, the significance value in the one sample t-test for the average cumulative abnormal return difference value is not significance. While the results of research on the Singapore Stock Exchange found no market overreaction phenomenon as indicated by a negative and insignificance average cumulative abnormal return difference. The result showed that the Indonesia Stock Exchange has not been efficient where investors tend to overreact in responding to information while investors on the Singapore Stock Exchange are rational.